2021
DOI: 10.3389/fpubh.2021.586670
|View full text |Cite
|
Sign up to set email alerts
|

A Vulnerability Analysis for the Management of and Response to the COVID-19 Epidemic in the Second Most Populous State in Brazil

Abstract: The COVID-19 pandemic has the potential to affect all individuals, however in a heterogeneous way. In this sense, identifying specificities of each location is essential to minimize the damage caused by the disease. Therefore, the aim of this research was to assess the vulnerability of 853 municipalities in the second most populous state in Brazil, Minas Gerais (MG), in order to direct public policies. An epidemiological study was carried out based on Multi-Criteria Decision Analysis (MCDA) using indicators wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…It is worth mentioning that the state of Minas Gerais was among the 10 federative units in the country with the highest rates of contamination [22]. Findings in the literature demonstrate a possible ineffectiveness of social isolation measures in some regions of Minas Gerais, such as the Jequitinhonha and Norte de Minas mesoregions, where economically disadvantaged people are more likely to live in housing with a high number of individuals, which, therefore, favor the risk of infection [23]. In addition to this social vulnerability, other factors, such as those of an economic and climatic nature, as well as the flow of transport, contribute to the understanding of the spread of the virus in this state [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the state of Minas Gerais was among the 10 federative units in the country with the highest rates of contamination [22]. Findings in the literature demonstrate a possible ineffectiveness of social isolation measures in some regions of Minas Gerais, such as the Jequitinhonha and Norte de Minas mesoregions, where economically disadvantaged people are more likely to live in housing with a high number of individuals, which, therefore, favor the risk of infection [23]. In addition to this social vulnerability, other factors, such as those of an economic and climatic nature, as well as the flow of transport, contribute to the understanding of the spread of the virus in this state [24].…”
Section: Discussionmentioning
confidence: 99%
“…Fragile socioeconomic conditions render people vulnerable to extreme conditions, and therefore also expose them more directly to the COVID-19 pandemic. As presented in Table 2 , a total of 10 social and economic variables are selected in this theme based on their relation to community vulnerability in the extant literature ( Campos et al, 2021 , Coven and Gupta, 2020 , Fortaleza et al, 2020 , Hossain et al, 2021 , Kashem et al, 2021 , Snyder and Parks, 2020 ). In the US, people’s poverty level is measured based on household or family income.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the metropolitan land area, population density, how populous a place is, its Human Development Index (HDI), and its Gini index (i.e., income inequality) have a positive association with COVID-19 prevalence ( Fortaleza et al, 2020 ). Similarly, another study ( Campos, Aratani, Cabral, Limongi, & Oliveira, 2021 ) from Brazil assessed vulnerabilities of 853 cities and concluded that high urbanization and population density, inadequate sanitation, high illiteracy, high Gini index, low HDI and household income, weak healthcare infrastructure, and a high number of people with underlying health conditions increased urban vulnerabilities to COVID-19 infection. Pourghasemi et al.…”
Section: Introductionmentioning
confidence: 99%
“…For better planning, it is crucial to find out areas that need special attention (Nisari et al, 2016). This purpose is served by conducting a vulnerability assessment done on various grounds using statistical methods (Nikolopoulos et al, 2021 ), vulnerability indices (Tuite et al, 2020 ; Campos et al, 2021 ) and geospatial techniques (Ali et al, 2021 ; Parvin et al, 2021 ). Researchers have also tried to assess the impact and modelled the vulnerabilities of COVID-19 on different part of the society (Daras at al., 2021) and various economic classes (Bidisha et al, 2021 ; Rahman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PCA has been utilised for modelling socio-economic as well as climatic vulnerability of COVID-19 (Salvacian, 2022). Multi-criteria decision-making (MCDM) was adopted for vulnerability assessments of Brazil (Campos et al, 2021 ) and Argentina (Özkaya and Özkaya, 2022 ). GIS and overlay techniques have been highly useful in the assessment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%